2022
DOI: 10.3389/fimmu.2022.810300
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and Potential Therapeutic Roles of Exosomes Derived From Immune Cells in Liver Diseases

Abstract: Liver diseases, such as viral hepatitis, alcoholic hepatitis and cirrhosis, nonalcoholic steatohepatitis, and hepatocellular carcinoma place a heavy burden on many patients worldwide. However, the treatment of many liver diseases is currently insufficient, and the treatment may be associated with strong side effects. Therapies for liver diseases targeting the molecular and cellular levels that minimize adverse reactions and maximize therapeutic effects are in high demand. Immune cells are intimately involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 128 publications
0
12
0
Order By: Relevance
“…An article by Nimitrungtawee et al 520 The main causes of these deaths are hepatocellular carcinoma (HCC), complications from liver cirrhosis, and viral hepatitis (VH). 521 A study by Zhou et al 521 focused on immune cell exosomes and their effects on liver disease treatments examining both the pathogenic and possible therapeutic functions of these exosomes in liver illnesses. Although the authors discussed the potential use of exosomes produced from different immune cell sources to treat liver disease, further study is necessary, particularly in human subjects.…”
Section: Therapeutic Intervention For Hepatocellular Carcinomamentioning
confidence: 99%
“…An article by Nimitrungtawee et al 520 The main causes of these deaths are hepatocellular carcinoma (HCC), complications from liver cirrhosis, and viral hepatitis (VH). 521 A study by Zhou et al 521 focused on immune cell exosomes and their effects on liver disease treatments examining both the pathogenic and possible therapeutic functions of these exosomes in liver illnesses. Although the authors discussed the potential use of exosomes produced from different immune cell sources to treat liver disease, further study is necessary, particularly in human subjects.…”
Section: Therapeutic Intervention For Hepatocellular Carcinomamentioning
confidence: 99%
“…42 Recently, it has been claimed that immune cells perform an essential effect in regulating hepatic fibrosis. 43,44 A study reported that a decrease in the number of γδ T cells in the peripheral blood and liver is significantly associated with the severity of fibrosis. 32 In addition, hepatic fibrosis might be regulated by cytokines and chemokines.…”
Section: γδ T Cells and Hepatic Fibrosis Cirrhosismentioning
confidence: 99%
“…This process is mainly driven by hepatic stellate cells (HSCs) with persistent inflammation in the liver 42 . Recently, it has been claimed that immune cells perform an essential effect in regulating hepatic fibrosis 43,44 . A study reported that a decrease in the number of γδ T cells in the peripheral blood and liver is significantly associated with the severity of fibrosis 32 .…”
Section: γδ T Cells and Hepatic Fibrosis Cirrhosismentioning
confidence: 99%
“…Exosomes from certain cell types inherit the surface proteins and contents of donor cells [14], which exhibit therapeutic properties, such as MSCs derived exosomes [15] and immune cellsderived exosomes [16]. Some researchers illustrated that the proinflammatory cytokines receptors in exosomes may act as a decoy for targeting inflammation therapy [17], others demonstrated that the secretion of exosomes will be increased during cellular inflammatory responses [18], which proved that exosomes can be used as therapeutic agents and the exosomal substances could also be used as markers for screening in inflammatory disease treatment [19].…”
Section: Introductionmentioning
confidence: 99%